Spatial Data Processing in Sustainable Land Use Planning - Lasaiba, Mohammad Amin; Alnursa, Darling Surya (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2023)
Sustainable land use planning requires the processing of spatial data to obtain accurate information about environmental conditions and the potential of available land. Spatial data is used at various stages of planning, from natural resource inventory, land use scenario development, impact evaluation, and decision-making of monitoring and assessment. However, the availability of adequate and high-quality spatial data remains a challenge in sustainable land use planning. Therefore, efforts are needed to improve access to and availability of spatial data, as well as to develop methods and technologies that can support the processing and analysis of spatial data. By optimally utilizing spatial data, sustainable land use planning can consider various aspects, such as environmental sustainability, socio-economic sustainability, and long-term benefits and public interests. This approach is expected to create sustainable land use, serving both current and future needs.